Treatment strategies and clinical outcomes in consecutive patients with locally advanced pancreatic cancer: A multicenter prospective cohort. (March 2021) - Walma, Marieke S.; Brada, Lilly J.; Patuleia, Susana I.S.; Blomjous, Joost G.; Bollen, Thomas L.; Bosscha, Koop; Bruijnen, Rutger C.; Busch, Olivier R.; Creemers, Geert-Jan; Daams, Freek; van Dam, Ronald; Festen, Sebastiaan; et al.
Abstract: Introduction: Since current studies on locally advanced pancreatic cancer (LAPC) mainly report from single, high-volume centers, it is unclear if outcomes can be translated to daily clinical practice. This study provides treatment strategies and clinical outcomes within a multicenter cohort of unselected patients with LAPC. Materials and methods: Consecutive patients with LAPC according to Dutch Pancreatic Cancer Group criteria, were prospectively included in 14 centers from April 2015 until December 2017. A centralized expert panel reviewed response according to RECIST v1.1 and potential surgical resectability. Primary outcome was median overall survival (mOS), stratified for primary treatment strategy. Results: Overall, 422 patients were included, of whom 77% ( n = 326) received chemotherapy. The majority started with FOLFIRINOX (77%, 252/326) with a median of six cycles (IQR 4–10). Gemcitabine monotherapy was given to 13% (41/326) of patients and nab-paclitaxel/gemcitabine to 10% (33/326), with a median of two (IQR 3–5) and three (IQR 3–5) cycles respectively. The mOS of the entire cohort was 10 months (95%CI 9–11). In patients treated with FOLFIRINOX, gemcitabine monotherapy, or nab-paclitaxel/gemcitabine, mOS was 14 (95%CI 13–15), 9 (95%CI 8–10), and 9 months (95%CI 8–10), respectively. A resection was performed in 13% (32/252) of patients after FOLFIRINOX, resulting in a mOS of 23 months (95%CI 12–34). Conclusion: This multicenter unselected cohort of patients with LAPC resulted in a 14 month mOS and a 13% resection rate after FOLFIRINOX. These data put previous results in perspective, enable us to inform patients with more accurate survival numbers and will support decision-making in clinical practice. Highlights: The majority of LAPC patients started anti-tumor treatment, mainly FOLFIRINOX (77%). mOS after FOLFIRINOX and (nab-paclitaxel/)gemcitabine was 14 and 9 months, respectively. There is no treatment paradigm after first-line treatment. A resection was performed in 13% of patients starting FOLFIRINOX, resulting in a mOS of 23 months. One out of 5 patients (22%) could undergo innovative therapies, mainly within clinical trials.